2023
DOI: 10.32884/ideas.v9i1.1117
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Lembar Kerja Peserta Didik Berbantuan Google Sites pada Materi Getaran, Gelombang, dan Bunyi

Abstract: Advances in technology as a support in terms of developing student worksheets is with the help of the internet. The research objective was to determine the quality (validity, practicality and effectiveness) of Google Sites-assisted student worksheets on Vibration, Waves and Sound material. The research refers to the 4-D Model development research namely Define, Design, Development, and Dissemination. After a limited trial was carried out by 20 class VIII students at SMP Negeri 3 Gorontalo, then an extended tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Previously, there had been research on developing learning media using the Google site on waves and sound material (Akuba et al, 2023;Ismawati et al, 2021;Ramadanti et al, 2023). However, the media provided still needs to be improved a lot, such as by not providing interactive simulations and evaluation questions (Pellas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, there had been research on developing learning media using the Google site on waves and sound material (Akuba et al, 2023;Ismawati et al, 2021;Ramadanti et al, 2023). However, the media provided still needs to be improved a lot, such as by not providing interactive simulations and evaluation questions (Pellas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The use of student worksheets with the help of Google Sites needs to be a guide for teachers because apart from making it easier for teachers and students to use them online, they can be used by students outside of school hours. (Akuba et al, 2023). The use of the Google site-based E-LKPD can also be used for other materials, so that teachers can adapt the material taught in the E-LKPD.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Google sites has been widely used in physics learning. The results of studies in previous research found that Google sites were used as a source of student learning (Mukti & Anggraeni, 2020;Putri et al, 2022;Rahmawati et al, 2022), aimed at increasing the ability to master concepts (Taufik & Doyan, 2022), improve learning outcomes (Akuba et al, 2023;Arrofi'uddin & Wulandari, 2022;Hasnaa & Sahronih, 2022;Wulandari et al, 2022), improve critical thinking (Rusli et al, 2022;Taufik & Doyan, 2022), increasing students' interest in learning (Bhagaskara et al, 2021), developing students' scientific attitude (Bhagaskara et al, 2021), as well as to improve students' problem-solving skills (Maryani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies in previous research show that educational theories applied in the development of teaching materials assisted by Google sites include problem solving (Maryani et al, 2022), guided inquiry (Bhagaskara et al, 2021), higher order thinking skills (Rusli et al, 2022), interactive multimedia (Wulandari et al, 2022). In addition, physics content that is the target of developing teaching materials assisted by Google sites includes vibration, wave, and sound material (Akuba et al, 2023;Maryani et al, 2022), motion dynamics (Rahmawati et al, 2022), particle dynamics (Arrofi'uddin & Wulandari, 2022), work and energy (Wulandari et al, 2022), weather (Bhagaskara et al, 2021), Newton's law (Putri et al, 2022), force and motion (Rusli et al, 2022), static electricity (Mukti & Anggraeni, 2020), harmonic vibration (Taufik & Doyan, 2022).…”
Section: Introductionmentioning
confidence: 99%